TO BUILD TRUST WITH EMPLOYEE AND GAIN THEIR LOYALTY AS THE KEY TO SUCCESS - See Lee Yen; Fadillah Ismail (Jurnal Penyelidikan Sains Sosial, 2021)
Employees are your most valuable assets. Organisations are highly dependent on employees' loyalty and expect their trust in the organization as a key ingredient factor. A successful company needs employees trust and who are loyal to what it stands for and to what it’s trying to achieve. Therefore, to ensure the sustainability and competitive advantage of an organization in facing the challenge of success, it is advised that employers examine several approaches that can be taken to win loyalty and build their trust and see the benefits and significant impact on the organization in the future. it is a step forward in creating organizational solutions and success